Cultura de segurança do paciente em terapia intensiva na perspectiva de profissionais de enfermagem - CAMPELO, Cleber Lopes (2018)
The promotion of safe care requires the understanding that it is strongly influenced of work culture, therefore, creating a safety culture is an important step to improving patient care, so this study aimed to describe the patient's safety culture from the perspective of nursing professionals in the intensive care unit of a hospital of the state helth network of São Luís, Maranhão. This is a descriptive exploratory type research with a quantitative approach, conducted in four intensive care units. The research population consisted of members of the nursing staff, totaling 163 participants. The data collection took place between September and October 2017, through the questionnaire Survey on Patient Safety Culture Hospital (HSOPSC), they were analyzed by statistical described for classifying areas strong, weak and potential for patient safety; the Cronbach's Alpha test was used to measure the reliability of the instrument and the Chi-Square test to evaluate statistical association among sociodemographic variables. The research was approved by the Ethics and Research Committee of the Federal University of Maranhão, with a substantiated opinion Nº. 2,076,153, and all the recommendations of resolution 466/12 were observed. Among the results, the Cronbach's Alpha was observed of 0.78, demonstrating a good reliability the majority of female students, 144 (89.4%), aged between 31 and 35 years (24.5%), were: high school (48.5%), followed by nurses who Post-Graduation Latu sensu (20.2%). Regarding the time of work in the profession, most have between five to ten years (47.6%) occupy the position of Practical Nursing (74.2%) and work with weekly working hours from 20 to 39 hours (87.7%). As for the dimensions evaluated in the study didn‟t identify any area classified as strong for patient safety; in relation to the dimensions classified as a potential area for patient safety, "Organizational learning and continuous improvement" stands out with (59.5%) positive responses, while the dimension "Openness of communication" stood out among the dimensions evaluated as weak for patient safety, with only (12.3%) positive responses. The general perception of patient safety was defined as very good (44.2%) by a majority of the participants. In relation to the number of reported events (68.7%) of the participants didn‟t report any safety related events in the last 12 months. The study indicates the need to develop a safety culture by the nursing teams of the intensive care units of the referred hospital.